Romantyczne doświadczenie Boga: człowiek i jego Stwórca w świetle korespondencji Zygmunta Krasińskiego = The romantic experience of God. Man and his Creator in the correspondence of Zygmunt Krasiński - Szuleko, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the picture of God and a human being emerging out of the epistolary legacy workof Krasiński, was presented. The individual presentation of the romantic`s perception of the Godand his creation led to the synthetic view of relations between them. In the 30`s and 40`s of thenineteenth century it was Krasiński`s main subject of consideration. Various ways of perceivingGod was analysed, evolving from God as the creator the merciful God to God - the punisher andthe destructor. In this work the emphasis was also put on the importance of a man as an individual,his transfiguration of personality and difficult way to sacrum. Moreover, the romantic writer in hiswork laid particular stress on the unity of God and humans.
Keywords: Krasiński, Zygmunt (1812-1859) - korespondencja; epistolografia - 19 w.